1992
DOI: 10.1111/j.1464-410x.1992.tb15624.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiazide Treatment for Calcium Urolithiasis in Patients with Idiopathic Hypercalciuria

Abstract: In a randomised trial based on a parallel design to determine the prophylactic effect of thiazide on stone formation, 210 calcium urolithiasis patients with idiopathic hypercalciuria were allocated either to treatment with trichlormethiazide (4 mg/day) or no treatment with only close follow-up; 35 patients were excluded for various reasons, including voluntary withdrawal. The background of the remaining 175 patients (82 in the thiazide group and 93 in the control group), including age and sex, was similar for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 24 publications
0
37
1
5
Order By: Relevance
“…Interestingly, in only 2 of 10 RCTs was hypercalciuria an inclusion criterion (9,14). Despite this fact, 7 of 8 trials of adequate duration showed a reduction of kidney stone-formation rate with thiazide diuretics.…”
Section: Thiazide Diuretics and Nephrolithiasismentioning
confidence: 99%
“…Interestingly, in only 2 of 10 RCTs was hypercalciuria an inclusion criterion (9,14). Despite this fact, 7 of 8 trials of adequate duration showed a reduction of kidney stone-formation rate with thiazide diuretics.…”
Section: Thiazide Diuretics and Nephrolithiasismentioning
confidence: 99%
“…Randomized-controlled trials have shown reductions in stone recurrence rates of up to 70% with thiazide diuretics [49]. Adverse effects that may offset any benefit are hypokalaemia (associated with reduced citrate excretion), hyperuricaemia, and hyperglycaemia.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…There are two placebocontrolled studies with thiazides [45,46], several others with control groups, and follow-up studies of patients with no comparable controls [47][48][49][50][51][52][53][54][55]. In one of the randomized studies thiazide was given together with magnesium and this regimen tended to be more effective than when thiazides were given alone [38].…”
Section: Thiazidementioning
confidence: 99%